Spectrophotometric Estimation of Losartan Potassium with Methylene Blue by Ion-Pair Extraction Method - Dawood, Asmaa Ghanim; Omer, Lazeeza Sattar (Iraqi Journal of Science, 2020)
A selective and sensitive spectrophotometric extraction method was established and used to estimate antihypertensive drug, losartan potassium. The method is based on the formation of blue ion pair of the anionic drug, losartan, and the cationic dye, methylene blue, at adjusted pH 6.5 in aqueous solutions, followed by quantitative extraction to dichloromethane;.The observed maximum absorbance was at Ï€ 654.9 nm. With 4.53321 x 105 M-1 cm-1 molar absorptivity, Beer's law was obeyed within a concentration range of 0.03-1.5 Î¼g / ml. The limit of detection and the limit of quantification were 0.01Î¼g / ml and 0.03Î¼g / ml, respectively. The method's precision was estimated by a relative standard deviation (0.725%-1.64%), and the accuracy was validated at a recovery range (98.48-100.3%). The proposed method was successfully used for estimating losartan in the pharmaceutical formulation and in the urine sample.